Successful limb-salvage procedure using a bioexpandable prosthesis after infected primary reconstruction of the distal femur in a skeletally immature patient: a case report - Lesensky, Jan; Belzarena, Ana C; Benes, Michal (World journal of surgical oncology, 2025)
BACKGROUND: Periprosthetic infections pose a devastating complication in skeletally immature patients treated for an orthopaedic oncological condition. Reconstructive approaches to revision procedures are often limited, and many cases still require amputation. CASE PRESENTATION: In this report, we present our unique experience with the bio-expandable MUTARS® BioXpand prosthesis, utilized during the second stage of a revision surgery in an adolescent female patient. Initially, the patient underwent reconstruction using a conventional endoprosthesis following the resection of a high-grade distal femur osteosarcoma; however, she developed a deep infection six months later. During a two-stage revision procedure, the infection was successfully eradicated at the cost of loss of growth potential at also the site of proximal tibia. The initial 5 cm limb-length discrepancy was restored through the application of bioexpandable endoprosthesis, which allowed for an 8 cm gain in bone stock. At the last follow-up appointment, the patient was fully weight-bearing and demonstrated excellent clinical outcomes, with no evidence of infection or tumor recurrence. CONCLUSION: This successful limb-salvage procedure indicates that bioexpandable endoprosthesis may serve as a viable and effective reconstructive option in revision surgery for skeletally immature individuals.
Keywords: Lengthening nail; Limb Salvage; Plastic Surgery Procedures; Female; Osteosarcoma; MUTARS® BioXpand; osteosarkom; Bone Neoplasms; ženské pohlaví; infekce spojené s protézou; Adolescent; lidé; Prosthesis-Related Infections; nádory femuru; nádory kostí; Femur; zákroky plastické chirurgie; prognóza; Reoperation; záchrana končetiny; reoperace; femur; Precise nail; Limb-salvage surgery; Periprosthetic infection; Knee revision; Prognosis; Bioexpandable prosthesis; mladiství; Femoral Neoplasms; Humans